2011
DOI: 10.1111/j.1744-7429.2011.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Regeneration of Tropical Dry Forest from Abandoned Pastures: Contrasting Chronosequence and Dynamic Approaches

Abstract: Old field secondary succession of tropical dry forests (TDFs) is poorly understood, particularly regarding the dynamics of seedlings, saplings, and sprouts (regenerative communities). We used chronosequence and dynamic approaches to: (1) document successional trajectories of regenerative communities during the first dozen years of regeneration in abandoned pastures at Chamela, Mexico; (2) test the usefulness of chronosequences to predict the dynamics of regenerative communities along time; and (3) assess the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 52 publications
6
52
1
8
Order By: Relevance
“…Also, they reduce the dominance of introduced grasses and promote seedling emergence (Lloret, 1998). Greater forest cover in the surrounding matrix has been associated to increased seedling recruitment (both in terms of species richness and number of individuals) in this region (Maza-Villalobos et al, 2011), as it contributes to higher propagule availability. These effects were orthogonal to those of the management regime components that foster forage production.…”
Section: Potential Synergies Between Site Conditions Management Regimentioning
confidence: 99%
“…Also, they reduce the dominance of introduced grasses and promote seedling emergence (Lloret, 1998). Greater forest cover in the surrounding matrix has been associated to increased seedling recruitment (both in terms of species richness and number of individuals) in this region (Maza-Villalobos et al, 2011), as it contributes to higher propagule availability. These effects were orthogonal to those of the management regime components that foster forage production.…”
Section: Potential Synergies Between Site Conditions Management Regimentioning
confidence: 99%
“…This produces a mosaic of vegetation patches comprising different ages of recovery ranging from 0 to 15 years as well as patches of old-growth forest. Based on extensive vegetation surveys conducted across a chronosequence in the region (Maza-Villalobos et al 2011;Ramos-López 2012), we classified our 23 study species into three successional status categories: early successional species, comprising specialists of the early successional stages (0-5 years of abandonment); mid-successional species, taxa entering the succession during intermediate stages of vegetation development (8-15 years of abandonment); and old-growth forest species, comprising taxa that successfully establish in late to old-growth forest but not in the early sites. The numbers and identities of species belonging to each successional group are shown in the Electronic Supplementary Material (Table S1).…”
Section: Study Systemmentioning
confidence: 99%
“…In a previous paper [41] we analysed successional patterns of these communities, which strongly suggested that temporal variation in rainfall plays a critical role in such dynamics. In that paper we showed that the observed patterns had no relation at all with understory light availability or with structural variables of the established woody communities (trees and shrubs with DBH ≥1 cm).…”
Section: Introductionmentioning
confidence: 99%